El género Leucocoprinus Pat. (Agaricaceae-Agaricommycetes) en el norte de Argentina y Paraguay - Campi Gaona, Michelle Geraldine (2015)
The genus Leucocoprius Pat. (Agaricaceae-Agaricomycetes)in northern Argentina and Paraguay. Five species of Leucocoprinus collectedrecently in northern Argentina and Paraguay were identifid. Four of them (L.birnbaumii, L. cepistipes, L. cretaceous and L. straminellus) are reported forthe fist time in Paraguay and Leucocoprinus birnbaumii, L. cepistipes and L.straminellus in northeastern Argentina. The range of L. cretaceous is expanded tothe Chaco and Formosa provinces (Argentina). The specimens are characterizedmorphologically, illustrated and a species identifiation key region is provided